THE ROLE OF ISLAMIC PROPAGATION SOCIETY INTERNATIONAL (IPSI) IN FACILITATING EFFECTIVE MOSQUE TOUR: AN ISLAMIC DA’WAH PERSPECTIVE ON INTERPERSONAL COMMUNICATION WITH NON-MUSIM TOURISTS - Aini, Zulkefli; Don, Abdul Ghafar; Kawangit, Razaliegh Muhamat; Ismail, A’Dawiyah; Puteh, Anuar (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study investigates the role of the Islamic Propagation Society International (IPSI) in guiding effective mosque tours, focusing on the implementation of Islamic da'wah through interpersonal communication with non-Muslim tourists. With the increasing globalization and inter-religious interactions, mosques have the potential to act as influential platforms for fostering understanding between Muslims and non-Muslims. However, there is a lack of systematic research on how these interactions are facilitated during mosque tours and the role of organized institutions such as IPSI in this process. The primary objective of this study is to analyze the communication strategies as well techniques employed by IPSI in engaging non-Muslim tourists to ensure informative and respectful mosque tours that align with Islamic da'wah principles. Utilizing a qualitative methodology, the research involved semi-structured interviews with IPSI tour guides especially the President of IPSI, as well as observational studies of mosque tours to collect rich, contextual data on the interpersonal dynamics at play and document analysis from several reading material related to the study. Findings reveal that IPSI's approach to mosque tours emphasizes empathetic communication, structured engagement, and the addressing of misconceptions, which are crucial in creating a positive and enlightening experience for non-Muslim visitors based on several steps of mosque tour. The study highlights the effectiveness of personal narratives and interactive dialogue in enhancing visitors' understanding of Islamic beliefs and practices. The significance of this research lies in its contribution to the field of intercultural dialogue, showcasing how structured da'wah efforts can serve as a bridge to foster greater appreciation and respect among diverse religious communities. The insights gained from this study can inform future strategies for Islamic organizations aiming to enhance outreach and promote harmonious interfaith relations through educational tourism.